Carrión's letters - Gavidia Ruiz, Ángel (2012)
Eighteen personal letters from Daniel Alcides Carrion were reviewed, providing some insight about his times in medical college, as well as his familial and social environment, the influence of the Pacific War and the hard times afterwards, and the last letters describe the illness that finally took his life.